2015
DOI: 10.1371/journal.pone.0141239
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental Changes in Composition and Morphology of Cuticular Waxes on Leaves and Spikes of Glossy and Glaucous Wheat (Triticum aestivum L.)

Abstract: The glossy varieties (A14 and Jing 2001) and glaucous varieties (Fanmai 5 and Shanken 99) of wheat (Triticum aestivum L.) were selected for evaluation of developmental changes in the composition and morphology of cuticular waxes on leaves and spikes. The results provide us with two different wax development patterns between leaf and spike. The general accumulation trend of the total wax load on leaf and spike surfaces is first to increase and then decrease during the development growth period, but these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 38 publications
(68 reference statements)
7
55
0
2
Order By: Relevance
“…The density and size of wax crystals were greater in high-wax lines than in low-wax lines ( Figure 2 ). Consistent with our results in cabbage, bloomed (waxy) leaves of sorghum and wheat have dense cuticular wax crystals, whereas bloomless (non-waxy) leaves have fewer wax crystals (Tarumoto, 2005; Wang et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The density and size of wax crystals were greater in high-wax lines than in low-wax lines ( Figure 2 ). Consistent with our results in cabbage, bloomed (waxy) leaves of sorghum and wheat have dense cuticular wax crystals, whereas bloomless (non-waxy) leaves have fewer wax crystals (Tarumoto, 2005; Wang et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…We found six chemical compounds in the cabbage waxes: alkanes, primary alcohols, aldehydes, secondary alcohols, ketols and ketones, but fatty acid was not present (Supplementary Table S2). In contrast to cabbage, low-wax broccoli contained 13.5% and high-wax broccoli contained 15.3% fatty acids (Lee et al, 2015), leaves and stems of wild-type Arabidopsis contained 8.36 and 1.37% (Lu et al, 2012), and leaves of wheat contained 0.5–11.0% fatty acids (Wang et al, 2015). In the present study, we observed dominant alkane chain lengths of C 27 , C 29 , and C 31 , similar to leaves of broccoli (Lee et al, 2015) and stems, leaves and siliques of Arabidopsis (Lee et al, 2009a); by contrast, C 30 alkane appears to be a unique component in cabbage compared to broccoli ( Figure 3 ; Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Grasses in the Triticeae tribe, subfamily Pooideae, which include the cultivated species barley (Hordeum vulgare; 2n = 2x = 14), rye (Secale cereale, 2n = 2x = 14), durum wheat (Triticum durum; 2n = 4x = 28, AABB), and bread wheat (Triticum aestivum; 2n = 6x = 42, AABBDD), have two predominant pathways for wax production: (i) an alcohol-and alkane-rich wax pathway and (ii) a pathway leading to β-diketones and derivatives including hydroxy-β-diketones (2). The alcohol and alkane waxes are prevalent in earlier development and on leaves, whereas β-diketones dominate during the reproductive phase, particularly on leaf sheaths and flower heads (3,4). β-Diketone wax is predominantly hentriacontane-14, 16-dione, which consists of a 31-carbon chain with carbonyl groups at C 14 and C 16 .…”
mentioning
confidence: 99%
“…Fuller and TAM 401 both have Jagger as a parent. In contrast, leaf wax n-alkanes have a long-carbon-chain aliphatic structure, and they are the first or second most abundant component in the leaf wax of many species ( Jetter and Schäffer, 2001;Wang et al, 2015). TAM 112 and Duster are the most drought-tolerant cultivars.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…Fannin and TAM 305 also share common parents (Ibrahim et al, 2015). n-Alkanes are not decomposed on the leaf surface after synthesis and harvest (Wang et al, 2015;Gamarra and Kahmen, 2017), which suggests potential for a convenient surrogate for assessing WUE l . Fannin and WB Cedar generally preform below the average in the High Plains due to the low winter temperature.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%